Teacher's Ability to Implement Mathematical Learning Variation Skills at MI PSM Gempolan II - Nafiul Kusna, Etin; Kurniawati, Eva (MANDAILING GLOBAL EDUKASIA, 2024)
Education has an important role in human life. The learning process of an education is organized actively, whereas if you do the same activity continuously it can cause boredom and lower the spirit of learning. In order to overcome boredom in students, teachers should make variations in learning, so that in learning and teaching situations, students always show perseverance, enthusiasm, and full participation. Learning activities have not gone well, this is due to the obstacles that occur during the learning process, especially in making variations. From the description above, the research problem can be formulated as follows (1) How is the implementation of how to teach teachers to use Variations in mathematics learning at MI PSM Gempolan II? (2) How do students respond to the variety of mathematics learning skills at MI PSM Gempolan II? The research method used is a qualitative descriptive research type. The subjects of the research are school principals, class teachers and class V students. The data collection techniques used are observation, interview, and documentation. The data sought in this research is the teacher's ability in classifying learning variations and student response. Data analysis techniques in this research include data collection, data reduction, data presentation, and drawing conclusions. The results of the research show the following findings (1) The teacher's ability to teach students by using learning variations is good, which can be seen based on indicators such as voice variations, teaching style, teacher and student interaction has begun to occur well, which can be seen from the student's learning motivation and evaluation results (2) Student response when implementing student learning variations is enthusiastic and enthusiastic. Students are not only recipients but givers of opinions can see students learn based on their own interests and abilities, the interaction between teachers and students has begun to be intertwined so that learning at school becomes more alive.